Production of fuel from waste tetra pak packaging in a fluidized bed: identification of factors that affect the mixture of sand particles and LDPE/AL composite - Selvatici Filho, Arthur Cesar; Mantegazini, Diunay Zuliani; Bacelos, Marcelo Silveira (Brazilian Journal of Production Engineering, 2021)
Integrated routes for catalytic pyrolysis and refining enable the conversion of polyolefins from post-consumer carton packaging waste into fuels and chemical products of commercial interest. This technology contributes to the reduction of environmental impacts resulting from the inappropriate disposal of these wastes. In addition, the recovery of the LDPE/Al composite (low-density polyethylene and aluminum) by pyrolysis allows obtaining products with high added values, such as paraffin and aluminum with high purity. The originality of this research is due to the development of a cylindrical column of fluidized bed with a guillotine system. Insertion of a guillotine system to cylindrical column allows evaluating the axial concentration of LDPE/Al composite particles. In addition, this research aims to investigate the effect of the air injection velocity and the mass fraction of LDPE/Al composite on the particle mixing index (Im), using an experimental design 3². The results show that the air injection velocity and the mass fraction of LDPE/Al composite affect the mixing index (Im). From point of view of particle mixing in the bed, data analysis indicates the fuel production from polyolefins is favored in the reactor when a gas velocity 25% above the minimum is used.